The Use Of Voice and Acting Game To Enhance Listening Ability In Narrative Text - Zeni Muzazizah (Journal Prakarsa Paedagogia, 2021)
Listening is one of English skills and it is one of the ways to learn English. Listening is more than merely hearing words. Listening is an active process from responding to spoken. Teaching listening skill is one of the most difficult skills for any ESL teachers. In fact, many students have difficulties in listening skill. They cannot understand and respond spoken English well especially by native speaker. The teacher must have a good creative technique to increase listening ability. Based on the fact above, the researcher thinks that it would be better using voice and acting game to solve the problem.  Voice and acting game is one of game in drama games. Voice and acting includes in free technique, which is the students listen and do acting what the teacher’s voice and  the dabbers’ voice. The design of this research is quantitative experimental research. The researcher uses one group pre-test post-test. The subject of this research are  32 culinary students of SMK Assa’idiyyah 2 Kudus in teaching narrative text. The result of this research indicates that there is significant difference between the listening ability of the tenth grade students of SMK Assa’idiyyah 2 Kudus  in 2020/2021 academic year before and after being taught by using voice and acting game . The result is  the maximum score is 95, and the minimum score is 60. The result of t-observation (to) is 17.87. Based on (df) 37 in the level of significance 0.05 t-table (tt) is 2.021. It means that t-observation is higher than t-table ( to > tt). It can be conclude that the use of voice and acting game is likely to improve the students’ listening comprehension skill.